Assessment Of The Performance Of The Tundish Of A Six Strand Continuous Casting Unit Of Com pan hi a Siderurgica Belgo-Mineira (CSBM), Brazil Using Physical Modeling - Mônica Suede Santos Silva (The Minerals, Metals and Materials Society, 2003)
This work describes characterization of the performance of the tundish of a six strand continuous casting unit of the Companhia Siderurgica Belgo Mineira, Joao Monlevade, Brazil using physical modeling. Permanent and transient conditions, due to ladle metal composition changes are considered. Pulse and step tracer addition techniques are employed to assess the control variables. For transient conditions the degree of inter-mixing and the minimum residence time are determined with a view to optimize the process especially during the grade changes of steel.